Testing MKTOR in Tanzania Universities [Pengujian MKTOR di Universitas Tanzania] - Ramadhani Kitwana Dau; Huda Ahmed Yussuf (DeReMa (Development Research of Management): Jurnal Manajemen, 2023)
The objective of the study was to determine the extent to which market orientation (MO) is related to university performance. The study was based on 212 respondents from private and public universities across Tanzania. Market orientation was measured by MKTOR. Structural Equation Model (AMOS 22) and SPSS were deployed for data analysis. Tests for reliability and validity showed that the measures have sound psychometric properties. Two hypotheses were tested and both were supported. This is the first study in Tanzania which is pan territorial drawing its sample from both public as well as private universities, notwithstanding the relatively low representation by private universities. This study is cross sectional. A longitudinal study would have provided a more appropriate explanation on underlying relationships over a period of time. Furthermore, in view of complexity of high education industry, mediating variables would have shaded more light on the relationship between the two constructs under different set of circumstances. Obvious practical implication is that universities should design programs that address wider customer needs which will make them a “go to” universities and in the process increase their reputation. High reputation will attract funding from different sources thereby giving the universities ability to offer scholarships to students. This will lead to increased access to university education and hence help the Government to solve some of social problems.Abstrak dalam Bahasa Indonesia. Tujuan dari penelitian ini adalah untuk mengetahui sejauh mana orientasi pasar (MO) terkait dengan kinerja universitas. Studi ini didasarkan pada 212 responden dari universitas swasta dan negeri di seluruh Tanzania. Orientasi pasar diukur dengan MKTOR. Model Persamaan Struktural (AMOS 22) dan SPSS digunakan untuk analisis data. Uji reliabilitas dan validitas menunjukkan bahwa langkah-langkah tersebut memiliki sifat psikometrik yang baik. Dua hipotesis diuji dan keduanya didukung. Ini adalah studi pertama di Tanzania yang merupakan pan teritorial yang mengambil sampelnya dari universitas negeri maupun swasta, meskipun perwakilan universitas swasta relatif rendah. Penelitian ini bersifat cross sectional. Studi longitudinal akan memberikan penjelasan yang lebih tepat tentang hubungan yang mendasari selama periode waktu tertentu. Selain itu, mengingat kompleksitas industri pendidikan tinggi, variabel mediasi akan lebih memperjelas hubungan antara dua konstruksi dalam keadaan yang berbeda. Implikasi praktis yang jelas adalah bahwa universitas harus merancang program yang menjawab kebutuhan pelanggan yang lebih luas yang akan membuat mereka menjadi universitas “go to” dan dalam proses meningkatkan reputasi mereka. Reputasi tinggi akan menarik pendanaan dari berbagai sumber sehingga memberikan kemampuan universitas untuk menawarkan beasiswa kepada mahasiswa. Hal ini akan mengarah pada peningkatan akses ke pendidikan universitas dan karenanya membantu Pemerintah untuk memecahkan beberapa masalah sosial.